Potency Analysis for Agro Science Techno Park Area Development Plan in Gorontalo Province - Wawan K. Tolinggi; Hayatiningsih Gubali; Mahludin Baruwadi; Amelia Murtisari (Hasanuddin University, 2018)
Global competitiveness index report in 2015 has put Indonesia in the 30th rank on one of the research collaboration performance between university and industry as innovation pillar. This indicates that there is still lack of synergy between higher education institutions and industry to develop research output. As the answer to this challenge, the Indonesian government initiated the establishment of Science Techno Park (hereafter, STP) as business technology incubator to stimulate and to manage the flow of knowledge and technology in universities, research and development institutions, industry, and government. However, among eight existing STP and 78 more that were planned to be built, Gorontalo, as an agricultural province with the potential to develop agro STP, was not among them. This study is aimed at examining the area potentials, potential commodities, and agro-industry potentials that are feasible for developing a pilot area for agro STP in Gorontalo province as a basis for implementation of agro-industry cluster policy to strengthen the regional innovation system in Gorontalo province. The data were collected from survey and focus group discussion (FGD). The data were analyzed by using Location Quotient Method and Exponential Comparison Method. The results reveal three potential agro-industry regency areas; Gorontalo Regency, Boalemo Regency, and Gorontalo Utara Regency as well as seven leading commodities for these potential areas; corn, coconut, marine fisheries, cocoa, beef cattle, cassava, and chili. Further, for agro-industry, the most dominant potentials to be developed are flour, beef floss, chips, handicraft, and animal feed.